2022
DOI: 10.1186/s12872-022-02654-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum sclerostin and osteoprotegerin levels with the presence, severity and prognosis in patients with acute myocardial infarction

Abstract: Background Bone-related proteins (such as sclerostin and osteoprotegerin [OPG]) are involved in the development of atherosclerosis. However, the relationship between bone-related proteins and acute myocardial infarction (AMI) has not been extensively evaluated. The purpose of this study was to assess the association of serum sclerostin and OPG with the presence, severity and prognosis in patients with AMI. Methods This study prospectively enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The main objective of this study was to assess the usefulness of possible biomarkers within the bone-vessel axis in patients with ACS. Our findings confirm the previously known relation between OPG and ACS patients 19 . However, neither OPG nor OPN values correlated with specific SYNTAX scores and only ORR showed a slight increase in the RR for high scores.…”
Section: Discussionsupporting
confidence: 93%
“…The main objective of this study was to assess the usefulness of possible biomarkers within the bone-vessel axis in patients with ACS. Our findings confirm the previously known relation between OPG and ACS patients 19 . However, neither OPG nor OPN values correlated with specific SYNTAX scores and only ORR showed a slight increase in the RR for high scores.…”
Section: Discussionsupporting
confidence: 93%
“…Although several clinical experiments have proved that OPG is closely related to CHD or AMI ( 9 , 21 , 27 ), and this relationship is positive, there is still controversy about this relationship in academic circles. In addition, other studies have found an association between OPG and other cardiovascular diseases, including congestive heart failure, aortic stenosis, and aortic valve calcification ( 8 , 28 ). At the same time, it is not only related to the occurrence of cardiovascular diseases, but also firmly to the prognosis of related cardiovascular diseases ( 29 33 ).…”
Section: Discussionmentioning
confidence: 95%
“…MI patients may benefit from the use of bone-related proteins for early risk stratification and prognosis evaluation. In patients with AMI, OPG levels are correlated with the complexity of coronary artery disease(CAD) ( 7 , 8 ). Healthy subjects with low or high coronary artery calcification cannot be distinguished by using OPG.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence indicating the predictive role of OPG in CAD risk stratification among various populations. For instance, in a recent study that patients with acute myocardial infraction (AMI) were recruited, OPG was an independent prognostic marker for major adverse cardiovascular events (MACE) during one year follow-up and was also positively associated with AMI [ 40 ].…”
Section: Discussionmentioning
confidence: 99%